Psychometric properties of the multidimensional assessment of interoceptive awareness (MAIA) in a Chilean population - Valenzuela-Moguillansky, Camila; Reyes-Reyes, Alejandro (Frontiers in Psychology, 2015)
The Multidimensional Assessment of Interoceptive Awareness (MAIA) is an instrument designed to assess interoceptive awareness. The aim of this study was to adapt the original MAIA scale to Spanish and to analyze its psychometric properties in a Chilean population. The MAIA was administered to 470 adults, aged 18 to 70 years, 76.6% women and 23.4% men, residents of the provinces of Valparaiso and Concepcion, Chile. Exploratory factor analysis reduced the scale from 32 to 30 items. Confirmatory factor analysis supports a structure of eight interrelated factors (Noticing, Not-Distracting, Not-Worrying, Attention Regulation, Emotional Awareness, Self- Regulation, Body Listening and Trusting), similar to the original scale (χ2(371) = 659.78, p = .0001; CFI = .92, TLI = .91, RMSEA = .056 and SRMR = .059). The Spanish version showed appropriate indicators of construct validity and reliability, with a Cronbach's alpha of .90 for the total scale, and values between .40 and .86 for the different subscales. Similar to previous studies, low reliability was observed in two of the eight scales (Not-Distracting and Not-Worrying), thus further revision of these subscales is suggested. The Spanish version of MAIA proved to be a valid and reliable tool to investigate interoceptive awareness in the Chilean population.